Outstanding Prevalence of Methicillin Resistant Staphylococcus aureus in Neonatal Omphalitis - Sengupta, Mallika (J Clin Diagn Res, 2016)
INTRODUCTION: Omphalitis is the infection of the umbilical cord stump, which can lead to septicaemia and significant neonatal morbidity and mortality. Very little data is available on the aetiology of neonatal omphalitis in India. AIM: To identify the causative agents of omphalitis in neonates and determine the antimicrobial susceptibility patterns of the isolates. MATERIALS AND METHODS: A prospective study was conducted at ESI-PGIMSR and ESIC Medical College, Joka, a tertiary care teaching hospital in Eastern India for a period of four months (from 1st January 2016 to 30th April 2016). Neonates were screened for omphalitis on the basis of presence of pus and redness for inclusion. Clinical examination, Gram stain and culture of umbilical discharge, identification of organisms by biochemical tests and VITEK 2 Compact (bioMereiux Inc., France) was done. Antimicrobial susceptibility by Kirby Bauer disc diffusion method and E-strip agar diffusion method (for vancomycin and teicoplanin) were performed and interpreted according to the Clinical and Laboratory Standards Institute (CLSI) guidelines version 2015. RESULTS: A total of 623 neonates were screened, among whom 21 (3.37%) were positive for our screening criteria for omphalitis. Cultures from the exudates of those cases yielded growth of Staphylococcus aureus in 19 (90.47%) samples, all of which were found to be methicillin resistant Staphylococcus aureus (MRSA). Resistance to erythromycin was seen among 36.82% isolates and inducible clindamycin resistance was seen among 31.57% isolates of Staphylococcus aureus. CONCLUSION: MRSA can be the most common cause of omphalitis. However, this finding needs to be evaluated in larger prospective studies.